Study on Legal Disputes over Audience Behavior in Sports Events: Taking the Olympic Table Tennis Fan Circle Incident as an Example - Luo, Jia (International Journal of Social Sciences and Public Administration, 2024)
A strong country is a strong country. The public’s attention to sports is not only reflected in personal fitness and exercise, but also in their attention to sports events. The recently concluded 2024 Paris Olympics has aroused the enthusiasm of the whole nation for the Olympics. The live broadcasts of various events have remained popular and are very popular. In addition to the lively atmosphere, there are also chaotic fan circles. This article focuses on the phenomenon of the Olympic Chinese table tennis fan circle, studies the improper behavior of the audience on social media and on-site viewing, puts forward corresponding legal regulations and governance suggestions, and makes a statement of view for the healthier development of sports events.